1994
DOI: 10.1111/j.1365-2141.1994.tb08312.x
|View full text |Cite
|
Sign up to set email alerts
|

The progression of HCV‐associated liver disease in a cohort of haemophilic patients

Abstract: We have studied morbidity and mortality related to hepatitis C virus infection in haemophilic patients treated at our centre. 11/255 HCV seropositive patients have developed hepatic decompensation. 20 years after first exposure to lyophilized clotting factor concentrate the risk of hepatic decompensation is estimated to be 10.8% (95% CI 3.8-17.8%). There is a significantly increased risk associated with HIV infection, and also with increased age. For HIV seropositive patients the rates of decline in CD4 lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
210
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(218 citation statements)
references
References 29 publications
6
210
1
1
Order By: Relevance
“…This is also in accordance with that reported in HIV-infected hemophiliacs, in which the risk of liver failure was 11-to 21-fold increased compared with HIV-negative patients and was associated with HIV-related immunodepression. 4,5 However, when considering only necroinflammatory liver lesions, we noted that HIV infection, but not the level of immunodeficiency (as assessed by a low CD4 cell count), was associated with an increase of lesions, suggesting that HIV may per se increase HCV-related liver damage. The mechanism involved in such a phenomenon remains to be determined.…”
Section: Discussionmentioning
confidence: 87%
“…This is also in accordance with that reported in HIV-infected hemophiliacs, in which the risk of liver failure was 11-to 21-fold increased compared with HIV-negative patients and was associated with HIV-related immunodepression. 4,5 However, when considering only necroinflammatory liver lesions, we noted that HIV infection, but not the level of immunodeficiency (as assessed by a low CD4 cell count), was associated with an increase of lesions, suggesting that HIV may per se increase HCV-related liver damage. The mechanism involved in such a phenomenon remains to be determined.…”
Section: Discussionmentioning
confidence: 87%
“…[1][2][3][4] Despite a decline in morbidity and mortality from opportunistic infections since the introduction of highly active antiretroviral therapy (HAART), end-stage liver disease continues to be a frequent cause of hospital admission and death in populations coinfected with HIV and hepatitis C virus (HCV). 5,6 For this reason, all HIVinfected individuals with positive HCV RNA determinations should be considered as candidates for anti-HCVtreatment, providing HIV infection is wellcontrolled and there are no contraindications to therapy with interferon or ribavirin.…”
Section: H Uman Immunodeficiency Virus (Hiv) Infectionmentioning
confidence: 99%
“…Subsequent studies indicated that progressive disease did occur [6,7] and that some patients presented with complications of cirrhosis [8]. These discrepancies may be explained by differences in the duration of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Cirrhosis was the primary or an associated cause of death in 8-11% of deaths in hemophilic patients [9,10]. Human immunodeficiency (HIV) co-infection is also an important contributor to the development of cirrhosis and liver failure [8,11].…”
Section: Introductionmentioning
confidence: 99%